IMPACT OF INFORMATION TECHNOLOGY AND MANAGEMENT SYSTEMS ON EMPLOYEE PERFORMANCE AT PT DAYA ADICIPTA - Gustaf Leonandri, Dino; Erpurini, Wala; Lesmana, Asep (Universitas Putera Batam, 2024)
This study aims to explore how Information Technology (IT) and Management Information Systems (MIS) influence employee performance. The research involves 115 respondents who are employees of PT. Daya Adicipta Motora Honda Dealer Baros in Cimahi City, using a stratified random sampling technique, which divides the population into strata to select samples. Data was collected through questionnaires and analyzed using multiple regression analysis. The processing of the questionnaire data using IBM SPSS Statistics 22 software shows that the Information Technology variable is valid based on the validity test, and the reliability test results for this variable are also deemed acceptable. Based on calculations using SPSS, the F-table value is 13.4. The SPSS output indicates the F-calculated value is 58.449, with a significance level of 0.000. Since the F-calculated value is greater than the F-table value and the significance level is less than 0.05, it can be concluded that Information Technology (X1) and Management Information Systems (X2) have a simultaneous and significant impact on Employee Performance (Y). This supports Hypothesis 3 (H3) of this study.